Skin and soft tissue modeling and its impact on apparel modeling - Carol McDonald; Randy K Rannow; Alfredo Ballester; Katy Schildmeyer; Emma Scott; Simeon Gill (Communications in Development and Assembling of Textile Products, 2023)
Rigid body avatars do not fully define the complex interaction between human and body-worn product (humanoid-to-coveroid).  Skin and soft tissue modeling to create more realistic 3D humanoid body models are needed. We considered if humanoid split lines relevant to pattern-engineering practice can be related to biodynamic and fold lines of the skin. Changes in skin and tissue are expected, depending on the dermis, the effects of movement, and the effects of coveroid pressure. The physiological functions of the skin may be assigned mechanical parameters for dynamic study utilizing biodynamic excisional skin tension (BEST) lines, main folding lines (MFL) with Langer’s lines. Critical to such study is the connecting of the skin to the rig (humanoid virtual skeleton). The use of stable (skeletal feature points related to both the virtual skeleton and apparel block patterns) and morphological (skin feature points identifying areas of morphological variation and dynamic study) landmarks for connecting the skin to rig was analyzed. We utilized these landmarks to drive lines as BEST, MFL and Langer’s lines for the mapping of skin deformations. Initial findings suggest the use of stable and morphological landmarks could have profoundly positive effects throughout the entire digital product creation (DPC) production pipeline and should be further explored & are important in developing standard topology practice.